Agonist-induced ADP-ribosylation of a cytosolic protein in human platelets. - Brüne, B (1990)
alpha-Thrombin and phorbol 12,13-dibutyrate stimulated the mono(ADP-ribosyl)ation of a 42-kDa cytosolic protein of human platelets. This effect was mediated by protein kinase C activation and was inhibited by protein kinase C inhibitor staurosporine. It also was prevented by prostacyclin, which is known to inhibit the phospholipase C-induced formation of 1,2-diacylglycerol, which is one of the endogenous activators of protein kinase C. On sodium dodecyl sulfate/polyacrylamide gel electrophoresis, the 42-kDa protein that is ADP-ribosylated by alpha-thrombin was clearly distinct from the alpha subunits of membrane-bound inhibitory and stimulatory guanine nucleotide-binding regulatory proteins, respectively Gi alpha and Gs alpha; the 47-kDa protein that is phophorylated by protein kinase C in platelets; and the 39-kDa protein that has been shown to be endogenously ADP-ribosylated by agents that release nitric oxide. This information shows that agonist-induced activation of protein kinase leads to the ADP-ribosylation of a specific protein. This covalent modification might have a functional role in platelet activation.